Subjective impacts of computerized cognitive training for healthy older adults in the context of the COVID-19 pandemic - Viviani, Cristiane Benedita Rodrigues da Mota Antunes; Ordonez, Tiago Nascimento; Pereira, Andreia Rodrigues; Jardim, Karen de Souza; Borges, Jonatas da Hora; Mota, Lais Aparecida Pereira; Santos, Gabriela dos; Moreira, Ana Paula Bagli; Verga, Cássia Elisa Rossetto; Ishibashi, Graciela Akina; Silva, Guilherme Alves da; Moraes, Luiz Carlos de; Lessa, Patrícia Prata; Gutierrez, Beatriz Aparecida Ozello; Brucki, Sonia Maria Dozzi; Silva, Thais Bento Lima da (Arquivos de Neuro-Psiquiatria, 2023)
Background Computerized cognitive training programs may have benefited the self-assessment of memory, quality of life, and mood among older adults during the coronavirus disease 2019 (COVID-19) pandemic.Objective To determine the subjective impacts of computerized cognitive training on mood, frequency of forgetfulness, memory complaints, and quality of life in the elderly using an online platform.Methods In total, 66 elderly participants of USP 60 + , a program for the elderly offered by Universidade de São Paulo, who voluntarily enrolled in the study were selected and randomized with an allocation ratio of 1:1 into 2 groups: the training group (n = 33) and the control group (n = 33). After signing the free and informed consent form, they answered a protocol which included a sociodemographic questionnaire, the Memory Complaints Questionnaire (MAC-Q), the McNair and Kahn's Frequency of Forgetfulness Scale, the Geriatric Depression Scale (GDS-15), the Geriatric Anxiety Inventory (GAI), and the Control, Autonomy, Self-Realization, and Pleasure (CASP-19) questionnaire. The training cognitive game platform aimed to stimulate various cognitive aspects, including memory, attention, language, executive functions (reasoning, logical thinking), and visual and spatial skills.Results The participants of the training group showed a reduction in the MAC-Q, MacNair and Kahn, and GAI scores in the pre- and posttest comparison. Significant differences were identified between the groups regarding the total scores of the MAC-Q in the post-test, which was also evidenced by the logistic regression.Conclusion Participation in a computerized cognitive intervention promoted reductions in memory complaints, frequency of forgetfulness, and anxiety symptoms, in addition to improving self-reported quality of life.
Keywords: Aged; Quality of Life; Cognitive Aging; Digital Technology; Cognition